A new species of deepwater wrasse (Labridae: Terelabrus) from the western Pacific Ocean - Fukui, Yoshino; Motomura, Hiroyuki (Zootaxa, 2015)
A new labrid fish Terelabrus dewapyle sp. nov. is described as the second species of the genus, on the basis of five specimens collected from southern Japan, Papua New Guinea, and Fiji in depths of 72–92 m. The sole paratype of T. rubrovittatus Randall & Fourmanoir 1998 is herein identified as T. dewapyle and designated as a paratype of the latter. The new species can be distinguished from T. rubrovittatus by the following characters: lower number of scale rows in the longitudinal series (41 or 42 vs. 45–48 in the latter), fewer pored lateral-line scales (39 or 40 vs. 43–45), and fewer gill rakers (12 or 13 vs. 14 or 15); a broader space between the anteroventral margin of the orbit and the maxilla [least distance 1.2–3.7% (mean 2.5%) SL vs. 0.5–2.3% (1.6%)]; no red blotches on the midlateral red stripe in adults and young (vs. 8–10 red blotches superimposed on midlateral red stripe in adults); no yellow band on the dorsal fin (vs. broad vivid yellow band submarginally on the dorsal fin in adults, pale yellow band in young); a vivid yellow (vs. white) space between the upper and midlateral red stripes; and a black blotch superimposed on the midlateral red stripe on the opercle in young, the black blotch fading with growth (vs. black blotch absent or indistinct).